2020
DOI: 10.1016/j.ijid.2020.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Performance of pneumonia severity index and CURB-65 in predicting 30-day mortality in patients with COVID-19

Abstract: The aim of the study was to analyze the usefulness of CURB-65 and the pneumonia severity index (PSI) in predicting 30-day mortality in patients with COVID-19, and to identify other factors associated with higher mortality. Methods: A retrospective study was performed in a pandemic hospital in Istanbul, Turkey, which included 681 laboratory-confirmed patients with COVID-19. Data on characteristics, vital signs, and laboratory parameters were recorded from electronic medical records. Receiver operating character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
140
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(178 citation statements)
references
References 22 publications
14
140
2
4
Order By: Relevance
“…In contrast, CURB-65, consisting of only five easily obtained parameters (mainly derived from vital signs), has been validated in different populations [14,16,17] and regarded as a strong predictor for mortality in CAP patients [8]. Celal Satici et al also found an excellent discrimination ability of CURB-65 for prediction of 30-day mortality in hospitalised patients, although it was outperformed by the more complex score system PSI [18]. In our study, CURB-65 demonstrated a good performance (AUC 0.81) and had a relatively large effect size (OR 4.11, 95% CI 2.10-8.02) for in-hospital death in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CURB-65, consisting of only five easily obtained parameters (mainly derived from vital signs), has been validated in different populations [14,16,17] and regarded as a strong predictor for mortality in CAP patients [8]. Celal Satici et al also found an excellent discrimination ability of CURB-65 for prediction of 30-day mortality in hospitalised patients, although it was outperformed by the more complex score system PSI [18]. In our study, CURB-65 demonstrated a good performance (AUC 0.81) and had a relatively large effect size (OR 4.11, 95% CI 2.10-8.02) for in-hospital death in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Various comorbidities were assessed and compared between two groups, except Medetalibeyoglu et al and Zheng et al studies which did not assess comorbidities of the subjects (12,13). The comorbidities that were more significantly common in the severe groups included cardiovascular diseases (i.e., coronary artery disease, heart failure) in ten studies (14-24), hypertension in nine studies (14, 16-19, 21, 22, 24, 25), chronic respiratory diseases in nine studies (17,19,20,(23)(24)(25)(26)(27)(28), diabetes mellitus in seven studies (11,16,18,21,22,25,29), cerebrovascular diseases in five studies (15,16,18,21,24), chronic kidney disease in four studies (18,(22)(23)(24), cancer in one study (25), and immunosuppression in one study (17). Four studies did not find significant association between the infection severity and the patients' comorbidities (30)(31)(32)(33).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Their score yielded an AUC of 0.74 for predicting ICU admission, and 0.82 for predicting mortality [8]. The well-known CURB-65 (C = Confusion, U = blood Urea nitrogen, R = Respiratory rate, 65 = age 65 or older) score and the Pneumonia Severity Index (PSI) have also been used on 681 laboratory-confirmed Turkish patients to predict mortality of COVID-19 related pneumonia with an AUC of 0.88 and 0.91, respectively [9]. All these scores were designed using multivariate regression models.…”
Section: Introductionmentioning
confidence: 99%